INNER CONFLICT AND IDENTITY CRISIS IN "BLONDE" BY JOYCE CAROL OATES (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Joyce Carol Oates’s novel Blonde (2000) offers a fictionalized portrayal of Marilyn Monroe that goes beyond biographical retelling to explore profound psychological and existential struggles. Central to the novel are themes of inner conflict and identity crisis, which shape the protagonist’s emotional life and ultimately lead to her fragmentation and self-destruction. Oates presents Marilyn—referred to alternately as Norma Jeane and “Blonde”—as a divided self, torn between private vulnerability and public myth. This thesis argues that Blonde depicts identity not as a stable construct but as a performance imposed by patriarchal, cultural, and cinematic forces. Through narrative fragmentation, symbolic doubling, and psychological realism, Oates exposes how fame, gender expectations, and trauma contribute to Norma Jeane’s internal conflicts and loss of authentic selfhood.